DNS - Pezet, Don; Bryan, Wes (Packt Publishing Ltd., 2024)
Dive deep into the world of DNS with this comprehensive course, meticulously designed to guide you through every aspect of DNS configuration and management. The journey begins with an exploration of DNS utilities, where you'll gain hands-on experience with tools like nslookup, dig, dnswalk, and dnsrecon, essential for troubleshooting and analyzing DNS records. Moving forward, the course covers the vital aspect of configuring email services through the setup of MX and SPF records, ensuring your email infrastructure is robust and secure. You'll then navigate the complexities of managing public domains, from purchasing and transferring domains to changing name servers, providing you with a comprehensive understanding of domain lifecycle management. The course also emphasizes the importance of DNSSEC for securing DNS information and its configuration using NSD. In the latter sections, you'll master zone replication across different DNS servers including NSD, Microsoft DNS, BIND, and Unbound. Each server-specific module covers installation, zone configuration, and replication strategies, ensuring you can manage DNS infrastructure across various platforms. The final section explores advanced topics like ad-blocking with Unbound and integrating it with BIND and NSD, equipping you with versatile skills to tackle any DNS challenge.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Internet domain names; Cloud computing; Client/server computing; Software configuration management; Architecture client-serveur (Informatique); Logiciels; Gestion de configurations; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet